Prenatal alcohol exposure and the associated risk of elevated blood pressure: a cross-sectional analysis of 3- to 17-year-olds in Germany - Arnold, Christine; Ullrich, Charlotte; Wensing, Michel; Bombana, Manuela (American journal of hypertension, 2019)
AbstractBACKGROUND. As the prevalence of obesity and high blood pressure increases among the population, early action is needed to reduce blood pressure. Certa
Published: 03 July 2019
Gesehen am 06.11.2019